Direct scribing of metal microgratings using sawtoothed cemented carbide tools with Johnson-Cook model-based plastic deformation simulation - Minwook Kim; Dae Bo Sim; Yong Tae Kim; Bo Hyun Kim; Jong G. Ok (Materials & Design)
We demonstrate the DISCRIM (DIrect SCRIbing of Metals) process for the continuous and scalable precision machining of metal micrograting structures, which utilizes direct mechanical scribing of a sawtooth–patterned cemented carbide tool edge over a metal workpiece. The tool edge is fabricated via sequential micro-grinding using a conical polycrystalline diamond tip prepared by wire electrical discharge machining. By operating the DISCRIM process under controlled force, temperature, and scribing speed, multiple microgrooves are continuously formed on the metal surface in a single stroke with highly uniform geometry. The process achieves a material removal rate of ∼36.4 mm3/min while maintaining groove-to-groove repeatability within ±8 % and limiting tool wear to less than 6 µm after ∼1.2 m of scribing. Finite element analysis and friction-based modeling, incorporating the Johnson-Cook plasticity framework, capture the substrate deformation response and predict depth errors below 5 %, complementing the experimental results and validating parameter-based depth control. The DISCRIM process requires only a small edge area of a high-hardness tool and operates without high-speed rotation, thereby enabling durable and high-throughput machining of large-area microstructures. Beyond metals, it is adaptable to temperature-sensitive polymers such as polycarbonate and polyimide, supporting scalable fabrication for functional surfaces and emerging applications in aerospace, electronics, and photonics.